Photoionization and photofragmentation of singly charged positive and negative Sc3N@C80 endohedral fullerene ions. Issue 20 (January 2020) - Müller, A; Martins, M; Kilcoyne, A L D; Phaneuf, R A; Hellhund, J; Borovik, A; Holste, K; Bari, S; Buhr, T; Klumpp, S; Perry-Sassmannshausen, A; Reinwardt, S; et al.
Synopsis: Photoprocesses of the endohedral fullerene ions Sc 3 N @ C 80 + and Sc 3 N @ C 80 − in the gas phase have been experimentally investigated with emphasis on the specific effects of the encapsulated trimetallic nitride cluster Sc3 N on the observed reaction yields. Clear evidence of photoexcitation near the Sc L edge is obtained with the dominating contributions visible in the one- and two-electron-removal channels. The experiments are accompanied by model calculations employing density functional theory (DFT).